2003
DOI: 10.1213/01.ane.0000057027.52664.0b
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Advanced Simulation in the Training of Anesthesiologists to Treat Chemical Warfare Casualties

Abstract: Advanced medical simulation can be used to train anesthesiologists to treat nonconventional warfare casualties. The limitations of medical performance in full protective gear can be learned from this training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…Previous studies have shown that even minimal protection gear causes difficulty in AW management efforts while performing ETI [10] and that full protection gear prolongs the time to ETI even among very skilled personnel [11,12]. This is probably due to adverse effects on vision, tactile abilities, and general performance [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that even minimal protection gear causes difficulty in AW management efforts while performing ETI [10] and that full protection gear prolongs the time to ETI even among very skilled personnel [11,12]. This is probably due to adverse effects on vision, tactile abilities, and general performance [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that 22 of the 25 participants (88%) agreed that the simulation scenarios were realistic and all 25 partic ipants found the simulation-based education model better than traditional training methods. 19 In a study to determine which IO devices were relatively easy to leam and use in the Special Operations environment, medical care providers attended a lecture explaining appro priate IO use, viewed videotapes on the injection models, and practiced with demonstration units in a classroom environment. Afterward, the study participants were randomly assigned one of the IO devices and asked to perform a sternal or tibial IO placement on a cadaver.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] The Canadian military categorizes simulation into technical, tactical, and strategic components. Technical simulation familiarizes troops with basic equipment and how to use it (i.e., weapons drills).…”
mentioning
confidence: 99%
“…Les forces armées à travers le monde ont utilisé la simulation pour l'entraînement opérationnel et les plans de secours. [2][3][4] Les militaires canadiens classent la simulation en catégories technique, tactique et stratégique. La simulation technique familiarise les troupes avec le matériel de base et la façon de l'utiliser (le maniement des armes).…”
unclassified